A randomized phase 2 study comparing EC or CMF versus nab‐paclitaxel plus capecitabine as adjuvant chemotherapy for nonfrail elderly patients with moderate to high‐risk early breast cancer (ICE II‐GBG 52). Issue 20 (25th June 2015) - von Minckwitz, Gunter; Conrad, Bettina; Reimer, Toralf; Decker, Thomas; Eidtmann, Holger; Eiermann, Wolfgang; Hackmann, John; Möbus, Volker; Marmé, Frederik; Potenberg, Jochem; Stickeler, Elmar; Simon, Eike; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Although greater than 40% of breast cancers occur in patients aged ≥65 years, these individuals are frequently undertreated. Taxane‐based adjuvant chemotherapy is considered the treatment of choice but to the authors' knowledge has only limited evidence in elderly patients. METHODS Patients aged ≥65 years with a Charlson comorbidity index ≤2 and pT1/2 pN0/1 disease and either human epidermal growth factor receptor 2 (HER2)‐positive, hormone receptor‐negative, grade 3 (according to Common Terminology Criteria for Adverse Events [version 3.0]), high uPA/PAI‐1 or any stage pT3/4 pN2/3 breast cancer were randomized to receive 4 cycles of adjuvant epirubicin and cyclophosphamide (EC) (epirubicin at a dose of 90 mg/m2 and cyclophosphamide at a dose of 600 mg/m2 intravenously [iv] on day 1 every 3 22 days) or 6 cycles of cyclophosphamide, methotrexate, and 5‐fluorouracil (CMF) (cyclophosphamide at a dose of 500 mg/m2, methotrexate at a dose of 40 mg/m2, and 5‐fluorouracil at a dose of 600 mg/m2 iv on days 1 plus 8 every 29 days) versus 6 cycles of nab‐paclitaxel and capecitabine (nPX) (nab‐paclitaxel at a dose of 100 mg/m2 iv on days 1, 8, and 15 every 21 days with 1 week of rest every 6 weeks plus capecitabine at a dose of 2000 mg/m2 orally on days 1‐14 every 21 days). Primary endpoints were treatment discontinuations and overall frequency of adverse events. RESULTS Thirteen of 198 patients (6.6%) discontinued EC/CMF and 69 of 193 patients (35.8%) discontinued nPX (P<.001) with 1 and 5 deaths observed during treatment, respectively. Grade 3 to 5 adverse events were more frequent among patients treated with EC/CMF (90.9%) than among those treated with nPX (64.8%) (P<.001), with hematological toxicities being more frequent with EC/CMF (88.4% vs 22.3%; P<.001), but nonhematological toxicities (hand‐foot syndrome, diarrhea, mucositis, fatigue, sensory neuropathy, thromboembolisms, and metabolic disorders) being more frequent with nPX (58.5% vs 18.7%; P<.001). None of the geriatric scores (Charlson comorbidity index, Vulnerable Elders Survey [VES‐13], Instrumental Activities of Daily Living [IADL], and G8) independently predicted grade 3 to 5 toxic events or treatment discontinuations. No differences in survival between the treatment groups were observed after 22.8 months. CONCLUSIONS Compared with EC/CMF, treatment with nPX led to more treatment discontinuations and nonhematological toxicities in elderly patients with moderate or high‐risk breast cancer. Cancer 2015;121:3639–3648. © 2015 American Cancer Society.